Providing Aquaponics Facility to the Kali Code Area of Yogyakarta to Support Food Availability for the Local Community - Ryan Anugrah Putra; Akhlisa Nadiantya Aji Nugroho; Habib Luthfi Ash Shiddiqie; Hafidh Naufal Ahmad; Himmah Mahmudah (Jurnal Inotera, 2022)
The community service program in the form of providing aquaponics facilities in the Kali Code area of Yogyakarta was implemented to support food availability in the community during the COVID 19 pandemic. This aquaponics facility is also expected to contribute to the development of the Kali Code region as an ecotourism area and an example of sustainable riverbank management. The water source used for the facility comes from the outlet of a wastewater treatment system that treats wastewater from several food stalls around the site. This is very beneficial in terms of conserving clean water resources as this aquaponics facility does not require a separate clean water supply. Several phases carried out in this program include the design, manufacture, and installation of aquaponics facilities. This program is also a means for students to explore ideas and use the skills they acquire during their studies to solve problems faced by the community. An example of how the program contributes to feeding the community is produced fish and vegetables are being used to support the consumption of the river school’s closing event at that location.